2003
DOI: 10.1515/znb-2003-0713
|View full text |Cite
|
Sign up to set email alerts
|

Flavones and New Isoflavone Derivatives from Microorganisms: Isolation and Structure Elucidation

Abstract: In the course of our chemical screening of actinomycetes and other bacteria from terrestrial and marine sources, several extracts showed colourless middle polar bands with strong UV absorption at 254 nm and brown to grey colouration with anisaldehyde/sulphuric acid. Working-up of such strains led to the isolation of a number of isoflavonoids. Daidzein (1a) and genistein (1b) are very wide-spread, however, compounds like kakkatin (2b, Streptomyces sp. GW39/1530) were known only from plant sources. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…528 In addition, the Streptomyces -derived actinoflavoside carries the rare 3′-amino-2′,3′,6′-trideoxy-ribopyranoside (α-D-ristosamine, 69 ) at C-7. 527 Intriguingly, while genistein rhamnosides lack antifungal activity, the corresponding talosides (talosins A and B) 532 were reported as potent antifungals, implicating the inversion of a single stereo-center (C-3′) within the appended sugar as the distinguishing feature that invokes antifungal activity.…”
Section: Flavonoids and Isoflavonoidsmentioning
confidence: 99%
“…528 In addition, the Streptomyces -derived actinoflavoside carries the rare 3′-amino-2′,3′,6′-trideoxy-ribopyranoside (α-D-ristosamine, 69 ) at C-7. 527 Intriguingly, while genistein rhamnosides lack antifungal activity, the corresponding talosides (talosins A and B) 532 were reported as potent antifungals, implicating the inversion of a single stereo-center (C-3′) within the appended sugar as the distinguishing feature that invokes antifungal activity.…”
Section: Flavonoids and Isoflavonoidsmentioning
confidence: 99%
“…Streptomycetes are capable of biotransformation of soybean meal as major organic medium components and production of various isoflavones [5][6][7][8][9][10][11][12][13][14][15]. In our search for new metabolites from actinomycetes, a new compound, 7-O-methyl-8-chlorogenistein (1), together with eight known isoflavones, 8-chlorogenistein (2) [10], kakkatin (3) [7], 7-O-methyl genistein (4) [7], genistein (5) [14], daidzein (6) [7], glycitin (7) [16], genistin (8) [17], and daidzin (9) [18], was isolated from the Streptomyces strain YIM GS3536, which was isolated from soil sample collected from Yunnan Province, P. R. China.…”
mentioning
confidence: 99%
“…Compounds 2-9 were known isoflavone derivatives. Their structures were identified as 8-chlorogenistein (2) [10], kakkatin (3) [7], 7-O-methyl genistein (4) [7], genistein (5) [14], daidzein (6) [7], glycitin (7) [16], genistin (8) [17], and daidzin (9) [18] by comparison of their spectroscopic data with those in the related literature. …”
mentioning
confidence: 99%
“…Comparison of the 1 H NMR spectra of 3 and the methylated derivative 3m revealed a supplemental methoxy group in 3m by a singlet appearing at δ H = 3.81 ppm. Amongst these derivatives, 3a and 3p are reported here for the first time whereas 3m was already described [7,9,12]. The results of the antibacterial assays indicated that neither the extract nor the isolated compounds have good activities.…”
Section: Samplesmentioning
confidence: 74%
“…Although compounds 2 and 3 were previously obtained from metabolism of daidzein and from microorganisms, respectively [9,10], it is the first time that these compounds are reported from a plant, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 94%